In silico prediction of human genes as potential targets for rice miRNAs. (August 2020) - Rakhmetullina, Aizhan; Pyrkova, Anna; Aisina, Dana; Ivashchenko, Anatoliy
Graphical abstract: Highlights: A highly complementary interaction of single and family osa-miRNAs with mRNAs of human genes was shown. The nucleotides of the binding sites of many osa-miRNAs in mRNA of the target genes are conservative compared to the flanking nucleotides. Most osa-miRNAs can affect target mRNA human genes involved in the development of some human diseases. Abstract: Background: Exogenous microRNAs (miRNAs) enter the human body through food, and their effects on metabolic processes can be considerable. It is important to determine which miRNAs from plants affect the expression of human genes and the extent of their influence. Method: The binding sites of 738 Oryza sativa miRNAs (osa-miRNAs) that interact with 17 508 mRNAs of human genes were determined using the MirTarget program. Result: The characteristics of the binding of 46 single osa-miRNAs to 86 mRNAs of human genes with a value of free energy (ΔG) interaction equal 94%–100% from maximum ΔG were established. The findings showed that osa-miR2102-5p, osa-miR5075-3p, osa-miR2097-5p, osa-miR2919 targeted the largest number of genes at 38, 36, 23, 19 sites, respectively. mRNAs of 86 human genes were identified as targets for 93 osa-miRNAs of all family osa-miRNAs with ΔG values equal 94%–98% from maximum ΔG. Each miRNA of the osa-miR156-5p, osa-miR164-5p, osa-miR168-5p, osa-miR395-3p, osa-miR396-3p, osa-miR396-5p, osa-miR444-3p, osa-miR529-3p, osa-miR1846-3p, osa-miR2907-3p families had binding sites in mRNAs of several human target genes. The binding sites of osa-miRNAs in mRNAs of the target genes for each family of osa-miRNAs were conserved when compared to flanking nucleotide sequences. Conclusion: Target mRNA human genes of osa-miRNAs are also candidate genes of cancer, cardiovascular and neurodegenerative diseases.